The Effectiveness Of The Digital Comic "Si Jali Children Of The City" For Improving The Independence Of Children 5-6 Years Old In Cahaya Desa Kindergarten Introduction Sumberjosari, Karangrayung District - Perdana, cindy; Rahmadani, Ni Kadek Aris (BELIA: Early Childhood Education Papers, 2024)
The purpose of this study was to determine the effectiveness of the digital comic "Si Jali Anak Kota" as a learning medium to increase the independence of children aged 5-6 years at Cahaya Kindergarten in Sumberjosari Village, Karangrayung District, Grobogan Regency. The method used in this research is quantitative experiment with one group pretest posttest design. The study population consisted of 32 children aged 5-6 years at Cahaya Kindergarten in Sumberjosari Village, Karangrayung District, Grobogan Regency. This study uses a total sampling technique in which the entire population is used as a sample. Research data collection techniques using observation, questionnaires and documentation. The data analysis technique uses inferential statistics by testing the hypothesis using the Paired Sample T-Test. The results of the research from the calculation of the t test obtained the value of |tcount| > ttable, namely 5.409 > 2.03452, with a significance value (2-tailed) of 0.000, then Ho is declared rejected and Ha is accepted. Based on the results of these calculations, the child's independence has increased by 16.84% from before the treatment using digital comic media "Si Jali Anak Kota". Calculation of the N-gain test obtained a result of 0.23 which strengthens that the effectiveness of digital comic media "Si Jali Anak Kota" can increase children's independence. These results indicate a change in the form of increasing the independence of children aged 5-6 years after being treated using digital comic media "Si Jali Anak Kota".